A socioeconomic and cost benefit analysis of Tropical Race 4 (TR4) prevention methods among banana producers in Colombia - Ritter, Thea; Álvarez, Diego; Mosquera, Leslie Estefany; Martey, Edward; Mockshell, Jonathan (2024)
The global banana industry faces a significant threat from Fusarium oxysporum f. sp. cubense Tropical Race 4 (TR4). While prior research has concentrated on TR4’s dissemination, reproductive conditions, and resistant banana varieties, this study employs a socioeconomic and cost-benefit analysis to explore the vulnerability of banana producers to TR4 in Colombia. It assesses the financial viability of current monitoring strategies and estimates potential losses in the event of TR4 spreading within the study area. Interviews were conducted with producers and key stakeholders in Colombia’s top two banana-producing departments, Antioquia and Magdalena. The findings reveal that farming systems are highly vulnerable to TR4, particularly due to the prevalent use of corms. Producers employ preventive measures such as cement paths, fences, disinfecting stations, and footbaths to counteract TR4’s spread. A cost-benefit analysis indicates that the benefits of these prevention methods significantly outweigh the associate